GIS-material for the archaeological project: The urban cultivated lands of Skänninge - Swedish National Heritage Board, UV Öst (Uppsala University, 2014)
The information in the abstract is translated from the archaeological report:
Due to the planned construction of a new train station in Skänninge, Mjölby municipality, the Swedish National Heritage Board's contract archaeology division, UV Öst, performed a preliminary investigation beside the existing station in November 2005. Skänninge is seen as being one of the central places of Östergötland County already in the Late Iron Age and Early Middle Ages. Recent excavations have also indicated that the place has had central functions already in the Early Iron Age. The historical maps show that the investigated area is situated on what was once cultivated land belonging to the city of Skänninge, at least from the 17th century and onwards. Most of the remains found during the excavating are connected to agriculture. A few features were found that might be older than the agricultural layers, but that are difficult to interpret. One of them, a shallow pit or the remains of cultural layer, has been dated to the late Bronze Age/early Iron Age. East of the railway are modern layers of soil, as thick as 2 m, probably originating from the construction of the railway at the end of the 19th century.

Purpose:

The information in the purpose is translated from the archaeological report:
The purpose of the preliminary investigation was to examine whether the development area contained any archaeological remains and, if so, to elucidate their scientific potential. The aim was to identify, document, interpret and characterize the features, cultural layers and possible constructions that could be affected by the development works.

The ZIP file consist of GIS files and an Access database with information about the excavations, findings and other metadata about the archaeological survey.

Riksantikvarieämbetet UV Öst genomförde i november 2005 en arkeologisk förundersökning i anslutning till stationsbyggnaden i Skänninge. Undersökningen föranleddes av att Mjölby kommun, i samband med utbyggnaden av järnvägen mellan Motala och Mjölby, planerar att anlägga en pendeltågstation i Skänninge. Skänninge har framhållits som en av Östergötlands centralorter redan under yngre järnålder och tidig medeltid. De senaste årens undersökningar har dessutom indikerat centrala funktioner redan under äldre järnålder i anslutning till det nu aktuella exploateringsområdet. Utifrån det historiska kartmaterialet kan det konstateras att förundersökningsområdet i alla fall från 1600-talet varit beläget på staden Skänninges stadsjordar.
Större delen av de lämningar som påträffades vid förundersökningen kan knytas direkt till agrar verksamhet. Vid undersökningen påträffades även ett mindre antal svårtolkade lämningar som skulle kunna vara äldre än den agrara verksamheten på platsen. En flack nedgrävning eller kulturlagerrest har daterats till yngre bronsålder/äldre järnålder. På östra sidan om järnvägen förekommer upp till två meter påförda massor från sen tid. Troligen har i alla fall delar av massorna tillkommit i samband med anläggandet av järnvägen i slutet av 1800-talet.

Syfte:

Informationen i syfte är hämtad ur rapporten för undersökningen:
Den arkeologiska förundersökningen syftade till att utröna om det aktuella exploateringsområdet omfattade bevarade äldre lämningar, och om så var fallet även fastställa de bevarade lämningarnas kulturhistoriska utsagovärde. Målsättningen med undersökningen var att identifiera, dokumentera, tolka och karaktärisera anläggningar, kulturlager och eventuella konstruktioner som kunde komma att beröras av det planerade exploateringsföretaget.

ZIP-filen innehåller GIS-filer samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen.
GIS-material för arkeologiskt projekt: Skänninges stadsjordar
Keywords: Iron Age; järnålder; historical period; historisk tid; Middle Ages; medeltid; HISTORY; HISTORIA; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive